Integer programming and combinatorial optimization : 18th International Conference, IPCO 2016, Liège, Belgium, June 1-3, 2016, Proceedings /: 18th International Conference, IPCO 2016, Liège, Belgium, June 1-3, 2016, Proceedings. (2016) - Unknown
No abstract available